Laser Thermal Input Effects on Deep Penetration CO2 Laser Welding of Carbon Steel - Mohammed Salih, Saad A.; Hamoudi, Walid K.; Hamoudi, Adel K. (Nahrain University College of Engineering Journal, 2012)
The present work brings forward a computational modeling of welding phenomena within an analytical framework. The aim is to study the effect of laser power and travel speed on the heat flow in keyhole laser welding and compare the experimental investigations with the theoretical model which was published formerly (ref.21,22). The problem is formulated and solved by approximating the laser beam as a point and a line heat source operating simultaneously. This concept produces weld profiles that have good qualitative agreement with the experiments. Mathematical model and computer program were constructed to solve two basic heat conduction equations for the moving point and line sources. The effect of coupling efficiency, thermal input and laser power loss on the welds parameters is presented.Key words: laser welding, thermal input, coupling efficiency, penetration depth